Screening diagnosis of primary immunodeficiencies in the practice of an allergist-immunologist - L. Y. Barycheva; L. S. Khachirova; V. A. Firsova; S. J. Farsijanc (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2023)
.